Migration networks and policy impacts: Insights from Romanian-Spanish migrations - Elrick, Tim; Ciobanu, Oana (Global Networks - A Journal of Transnational Affairs, 2009)
Migration networks are now generally recognized as a means of adapting to or circumventing states' migration policies, but little research has been carried out on quite how they work. In this article, we analyse migrant networks between Romanian and Spain over the last 20 years. We contrast two villages to reveal how different reactions to policy changes depend on the level of development of migration networks. Among these policy changes are regularizations of irregular migrants in Spain, the visa-free entry of Romanians into Schengen countries enacted in 2002, EU enlargements in 2004 and 2007, and a bilateral agreement on labour recruitment between Romania and Spain. We conclude that networks can help migrants circumvent restrictive policies, foster the effective take-up of permissive policies or even impede them, depending on the development of the migration networks of the communities.
Keywords: migration networks; migration theory; Romanian migration; labour migration; migration industry